The Analysis of Teachers’ Strategies in Teaching Reading - Wael, Ahmad; Hardianti, Rinda; Uluelang, Kris; Rumakey, Aminah (JOLIES : Journal of Linguistic and English Studies, 2025)
Reading comprehension is the ability to understand the ideas and information in the reading text. Reading comprehension is very important because without good understanding students misunderstand the text they are reading. Students can understand the reading text but it depends on the strategies used by the teachers, because strategy is one of the factors involved in reading comprehension. The purpose of this study was to determine the teacher's strategy in teaching reading comprehension at MTs Sains Algebra Kota Sorong. To collect the data, the researchers used oservation and interview. Obseravtion was used in teaching activity while the interview was used at the end of teaching activity. The reserachers used qualitative descriptive design in order to obtain the the data. The participants were two English teachers. The participants were two English teachers. Researcher collect data through observation and interviews. Researchers use qualitative research methods and qualitative descriptive design.The results of this research are two English teachers applied same strategies in teaching reading comprehension, namely Scaffolding strategy and QARs strategy.